2013
DOI: 10.1016/j.ecss.2013.02.017
|View full text |Cite
|
Sign up to set email alerts
|

The use of nematodes in assessing ecological conditions in shallow waters surrounding a Mediterranean harbour facility

Abstract: a b s t r a c tThe spatial distribution and structure of nematode assemblages in the area surrounding the harbour of Vado Ligure (Savona, NW Mediterranean) were studied in relation to the influence of natural and anthropogenic environmental factors. Stations were selected following an "anthropogenic gradient" from sites located near the city centre and its harbour to more pristine and distant sites. Sediment quality was determined by considering both sediment granulometric and chemical parameters (hydrocarbons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 70 publications
5
29
1
1
Order By: Relevance
“…Such treatments might promote the natural recovery of ecosystems. Additionally, our results confirm the potential use of nematodes for assessing the ecological conditions of coastal environments (Losi et al 2013) since it was the sole meiofaunal group present in all treatments throughout the present experiment.…”
Section: Discussionsupporting
confidence: 87%
“…Such treatments might promote the natural recovery of ecosystems. Additionally, our results confirm the potential use of nematodes for assessing the ecological conditions of coastal environments (Losi et al 2013) since it was the sole meiofaunal group present in all treatments throughout the present experiment.…”
Section: Discussionsupporting
confidence: 87%
“…They found that the latter proved to be the best tool for the evaluation of EcoQ status. Other studies found that the analysis of nematode assemblages at the genus level represents the most informative tool in relation to the EcoQ: in the study of Losi et al (2013a) the analysis of the nematode assemblage at the level of genus revealed the best connection between environmental status and biological response, and in Losi et al (2012) only the genera analysis brought to light early changes in the community due to the touristic pressure. The same results are reported by Vezzulli et al (2008) and Mirto et al (2014) in relation to the fish farm impact and by Schratzberger et al (2009) in relation to physical stress.…”
Section: Taxonomic Structurementioning
confidence: 99%
“…Harbours are exposed to multiple contaminants such as toxic compounds, trace elements, hydrocarbons and OM (Losi et al, 2013a). Given the increasing occurrence of problems to marine life and human health associated with harbours and all the implications for the EcoQ status, several studies on the effects of the harbours' environmental conditions on nematode assemblages were conducted in the Ligurian Sea Moreno et al, 2008aMoreno et al, , b, 2009Losi et al, 2013a,b) (Fig.…”
Section: Trace Elements and Hydrocarbonsmentioning
confidence: 99%
See 2 more Smart Citations